Case Study: Physical Mobility Impairments in Elderly Gout Arthritis Through A Combination Therapy - Otaviani, Olvy Oriska; Devi, Hilda Mazarina; Maemunah, Neni (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
The increase in uric acid levels in the elderly (gout arthritis) can cause physical mobility impairments, requiring the role of nurses to address them. The aim of this study is to implement nursing care for physical mobility disorders through a combination therapy of warm ginger compresses and Range of Motion (ROM) exercises at Rumah Asuh Anak Lansia Griya Asih Lawang. The study design is a case study. The respondents were three elderly individuals with gout arthritis. The nursing interventions provided included identifying pain or other physical complaints, assessing physical tolerance for movement, monitoring blood pressure before starting mobilization, monitoring general conditions during mobilization, facilitating mobilization activities with assistive devices, providing non-pharmacological techniques to reduce pain (warm ginger compresses) for 10 consecutive days, facilitating ROM exercises for 10 consecutive days, explaining the objectives and procedures of mobilization, and teaching simple mobilization techniques to be performed. After intervention and nursing approach for 10 days, physical mobility disorders decreased as indicated by a decrease in acid levels in patient 1 with a value of 10.2 mg/dl, patient 2 9.4 mg/dl and patient 9.8 mg/dl as well as muscle strength in patients 1 5/5 and 5/4, patient 2 5/5 and 4/5, patient 3 5/4 and 4/4.  Warm ginger compress therapy and ROM exercises can be used as an intervention to reduce physical mobility disorders